QUALITY MANAGEMENT OF EDUCATION OF DAI CADERIZATION (CASE STUDY AT STID MOHAMMAD NATSIR) - Yudhita Omayra (Jurnal Bina Ummat: Membina dan Membentengi Ummat, 2022)
This study aims to describe the quality management of preaching cadre education at the Mohammad Natsir College of Da'wah (STID). The research method used is approachanalytical descriptive. The results of the study show that first, the competence of graduates formulated by the institution is in accordance with the needs of students who are cadres to become preachers. Second, the management function in academic services at STID Mohammad Natsir has been implemented, namely by the stages of planning, organizing, implementing, and controlling. Third, that the academic service management system that runs at STID Mohammad Natsir is still not optimal to produce graduates who have the competence as preachers in accordance with the competencies formulated by the higher education institution. The recommendation is that an ongoing quality management system should be carried out in totality and ensure that each management function has been carried out properly.